The Political Economy of Food System Transformation Pathways to Progress in a Polarized World - Resnick, Danielle; Swinnen, Johan (Oxford University Press, 2023)
Although the global food system increasingly is viewed as unsustainable for human and planetary health, the policy pathways for transforming the status quo are often highly contentious. This book brings together inter-disciplinary scholars to analyze the political economy dynamics central to food system transformation and to identify pathways for enhancing the political feasibility of necessary reforms. Drawing on original surveys, interviews, empirical modeling, and case studies from around the world, the book delves into the power dynamics, interest group coalitions, narratives, and institutional structures that shape decisions related to agricultural productivity, agro-industry, trade, and food consumption.